2020
DOI: 10.21203/rs.3.rs-16666/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Timing of optimal surgical intervention for vitreous hemorrhage in patients with proliferative diabetic retinopathy

Abstract: Background:To explore the optimal timing of vitrectomy for vitreous hemorrhage in the patients with proliferative diabetic retinopathy (PDR).Method:Seventy-six PDR patients (85 eyes) who were diagnosed with vitreous hemorrhage and received vitrectomy were retrospectively enrolled into this study. The patients were categorized into 4 groups based on the timing of surgical intervention after the occurrence of hemorrhage, namely Group 1 (less than 15 days, with 28 eyes of 27 patients), Group 2 (15~30 days, with 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The results of DRVS showed that eyes undergoing early vitrectomy for severe vitreous haemorrhage were more likely to have VA ≥ 20/40 at 2 years and greatest benefit was seen in patients with type 1 diabetes [10]. With the evolution of better surgical techniques and instruments (MIVS), early vitrectomy is more effective in achieving better visual outcomes [11]. Usually, patients with type 1 or type 2 diabetics with VH and no underlying traction, can be observed for 1 month [12].…”
Section: Timing Of Vitrectomy In Diabetic Vitreous Haemorrhagementioning
confidence: 99%
“…The results of DRVS showed that eyes undergoing early vitrectomy for severe vitreous haemorrhage were more likely to have VA ≥ 20/40 at 2 years and greatest benefit was seen in patients with type 1 diabetes [10]. With the evolution of better surgical techniques and instruments (MIVS), early vitrectomy is more effective in achieving better visual outcomes [11]. Usually, patients with type 1 or type 2 diabetics with VH and no underlying traction, can be observed for 1 month [12].…”
Section: Timing Of Vitrectomy In Diabetic Vitreous Haemorrhagementioning
confidence: 99%